2012
DOI: 10.1515/hsz-2011-0259
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A5 internalized by human adipocytes modulates cellular triglyceride content

Abstract: Apolipoprotein A5 (apoA5), an important determinant of plasma triglyceride (TG) levels, has been recently reported to modulate TG metabolism in hepatocytes. In this study, we investigated whether apoA5 can be internalized by adipocytes and regulate cellular TG storage. Human preadipocytes, derived from subcutaneous adipose tissue of patients undergoing abdominal surgery, were differentiated into mature adipocytes. Pulse-chase experiments revealed that apoA5 was internalized into human adipocytes, and ∼70% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 0 publications
4
32
0
Order By: Relevance
“…Interestingly, apoA5 in hepatocytes is also localized on the surface of cytoplasmic LDs (Shu et al, 2007) and has proved to be an important modulator in cellular TG and lipoprotein metabolism (Shu et al, 2010). As expected, after incubation of human adipocytes with recombinant human apoA5 proteins, we observed an obvious reduction in cellular TG content (Zheng et al, 2012). As expected, after incubation of human adipocytes with recombinant human apoA5 proteins, we observed an obvious reduction in cellular TG content (Zheng et al, 2012).…”
Section: (2) Apoa5supporting
confidence: 68%
“…Interestingly, apoA5 in hepatocytes is also localized on the surface of cytoplasmic LDs (Shu et al, 2007) and has proved to be an important modulator in cellular TG and lipoprotein metabolism (Shu et al, 2010). As expected, after incubation of human adipocytes with recombinant human apoA5 proteins, we observed an obvious reduction in cellular TG content (Zheng et al, 2012). As expected, after incubation of human adipocytes with recombinant human apoA5 proteins, we observed an obvious reduction in cellular TG content (Zheng et al, 2012).…”
Section: (2) Apoa5supporting
confidence: 68%
“…Studies have shown that plasma levels of ApoA5 are reduced in obese subjects and inversely correlated with measures of insulin resistance [53]. In hepatocytes and adipocytes, ApoA5 localizes on the surface of cytoplasmic lipid droplets, and incubation with ApoA5 has been shown to reduce cellular triglyceride content in human adipocytes [54,55]. ApoM overexpression has been shown to improve insulin sensitivity in rats [56] and ApoM was found to be upregulated by all berries, except açai, which downregulated ApoM.…”
Section: Lingonberries Blackcurrants Bilberries and Açai Exert Theimentioning
confidence: 99%
“…These results suggest that ApoA5 might induce a decrease in VLDL associated TG levels by both decreasing hepatic VLDL synthesis and increasing VLDL clearance. Besides, a recent study showed that ApoA5 may be absorbed by human adipocytes and may play a role in TG storage regulation [21]. …”
Section: Introductionmentioning
confidence: 99%